Optimising soybean molasses in broiler feed diet: influence on pelleting process and pellet physical quality - Viktor Stojkov; Slađana Rakita; Vojislav Banjac; Dušan Rakić; Aleksandar Fišteš; Strahinja Vidosavljević; Luciano Pinotti (Italian Journal of Animal Science)
The aim of present study was to determine the effect of soybean molasses (SBMo) on broiler feed pellet production and the physical quality of the pellets, as well as to compare SBMo with other binders. The experiment was divided into two stages. Stage I focused on optimising pelleting input parameters: SBMo inclusion level in feed (10, 30, 50 g/kg), sieve opening diameter of the hammer mill – SOD (1, 2, 3 mm), and moisture content – MC (130, 150, 170 g/kg) of the mash before pelleting, to achieve minimal specific energy consumption (SEC) of the pellet press while maximising the physical quality of the pellets. The optimisation showed that the most optimal values of input parameters were: SBMo content of 50 g/kg, SOD of 1 mm, and MC of 130 g/kg. The optimised input parameters were guidelines for comparing the efficiency of SBMo, sugar beet molasses (BM), and a commercially available surfactant as pellet binders in broiler diets with and without steam conditioning. Additionally, when steam was not used in the pellet production process, the inclusion of 50 g/kg of SBMo in broiler pellets reduced SEC by 20%, while also decreasing PH, PDI, and BD. Steam conditioning resulted in a 30% reduction in SEC when SBMo was included in the diet, without compromising QoF, PDI, or BD. BM had no effect on SEC, while the commercial surfactant reduced SEC by 13% compared to the control diet. Pellets produced with steam conditioning had better physical quality than those produced without steam.